Linguagem do design de hipermídia sob o enfoque sistêmico-funcional: a organização da informação em homepages de cinco revistas de arte e cultura produzidas nos BRICS - Nascimento, Marisa (2015)
The aim of this study is to investigate the organization of information on art magazine home pages through its design. In cyberspace complex environment, communication processes are developed through multiple semiosis such as images, words, audios and videos, interacting within a composition to encompass content and construct meaning. Such meanings can be recovered in multimodal analysis, given that navigation in hypermedia is based in form, structure and aesthetics of the virtual environment. The study of the organization of information in homepages is based on Systemic Functional Theory (SFT) and Multimodal Discourse Analysis (MDA). By focusing on language functions and their use in the sphere of human relations, the concepts of SFT underlie useful analyzes of the meaning that emerges from the text. The systemicfunctional approach is not restricted to verbal language, and it can be applied to other semiotic systems. In this sense, MDA contributes to understand hypertext entailments from the hypermedia design that organizes the information. The corpus of this study consists of sample homepages of five art magazines from the BRICS: Bravo!, from Brazil; Iskusstvo , from Russia; ART India, from India; LEAP (艺术界), from China; and Art Times, from South Africa. As a research methodology content analysis is employed, in order to identify variations and patterns that occur in the corpus, developing rank scales for the homepages components. During the analysis, homepages are compared with each other and with practical examples of web design, developed in specific literature in the areas of Graphic Design, New Media Design and Information Technology. The organization of information analysis in homepage genre under the systemicfunctional approach, as well as the discussion of previous studies from this perspective are the contributions launched by this study. The results show that the five homepages have similar systems in terms of visual and web design grammar, despite its accomplishments are distinct. The survey also points out that it is necessary to pay attention to the fact that emerging countries are emphasizing not only the economy but also by various trends, such as media content production focused on the arts and developments in hypermedia design issues. This is a study linked to SAL Project (Systemic Across Languages), which analyzes the language in use in numerous text genres and different languages, and it is developed in partnership with universities in Brazil, Argentina, China, Japan, Thailand, Mexico and Colombia. This study contributes to SAL Project, once it is the first hypermedia design language analysis being investigated among researchers in the project